2018
DOI: 10.1017/jgc.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of Resilience in Predicting Cyber Bullying Perpetrators and Their Victims?

Abstract: This study examined the role of resilience in the lives of cyberbullying perpetrators and their victims. Turkish adolescents (n = 444; 245 girls, 55.2%, and 199 boys, 44.8%) 15–19 years of age (mean age of 16.58 years, SD = 0.789) were recruited from different high schools. The participants completed the Cyberbullying Scale (Arıcak, Kınay, & Tanrıkulu, 2012), the Cybervictimisation Scale (Arıcak, Tanrıkulu, & Kınay, 2012), and the Child and Youth Resilience Measure (Arslan, 2015). The data were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
3
12
0
1
Order By: Relevance
“…Resilience was found to be a significant predictor of both the cyberbullying and cyber victimization as a result of the study. In their study conducted with 444 adolescents, Kabadayı and Sarı [37] researched the role of resilience on cyber bullying and victimization, and suggested that resilience significantly predicted cyber bullying and victimization, similar to this study. Hinduja and Patchin [38] stated that resilience was a strong protective factor on cyberbullying in their study conducted with 1204 adolescents.…”
Section: Discussionsupporting
confidence: 78%
“…Resilience was found to be a significant predictor of both the cyberbullying and cyber victimization as a result of the study. In their study conducted with 444 adolescents, Kabadayı and Sarı [37] researched the role of resilience on cyber bullying and victimization, and suggested that resilience significantly predicted cyber bullying and victimization, similar to this study. Hinduja and Patchin [38] stated that resilience was a strong protective factor on cyberbullying in their study conducted with 1204 adolescents.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the relationship between resilience and bullying, few studies have analyzed the mediation effect of resilience on the victimization process. The work performed by Navarro, et al [25] with adolescent students found that resilience had a moderating effect on victimization by cyberbullying, such that it was shown to be a "protector" against victimization, in line with the results of another study that analyzed the predictive power of resilience on cyberbullying [26] in 377 Turkish students aged 15 to 19, in which a simple regression analysis revealed that resilience negatively predicted cyberbullying perpetration and cybervictimization. The results of Hinduja and Patchin [16], in another work performed with American students aged 12 to 17, indicated resilience as a powerful protective factor, both to prevent experiences of intimidation and to mitigate their effect, in line with the claims of other authors [8] who already suggested the possible protective nature of resilience in such situations, or as in the work of Moore and Woodcock [27], in which students with poorer resilience were more prone to engage in bullying behaviors as well as to become victims.…”
Section: Introductionmentioning
confidence: 60%
“…(2) The CS will be positively related to and will positively predict bullying behaviors as in a study with Estonian students between 12 and 16 years [58]. 3Resilience will be negatively related to and will negatively predict victimization as in previous studies on traditional bullying [24,25,27,28] and cyberbullying [26].…”
Section: Introductionmentioning
confidence: 93%
“…Resilience in relation to cyberbullying (perpetration and victimization) in Turkey (Kabadayi & Sari, 2018):…”
Section: Example Of Recent Usementioning
confidence: 99%